(untitled) (Academic Journal of Internal Affairs, 2021)
This book, which the dear reader takes with interest in his/her hands, is not written in the usual style, although in terms of its content it can be said that it is a well-crafted volume of studies. The topic itself is not ordinary. The term ‘SZEM’ model certainly reminds many people of something else than solid morality measurement. However colleagues with knowledge in academia, on the other hand, will know that we are talking about Ajzen and Fishbein’s model, one of the known theories of predicted behavior for predicting behavior (e.g., unhealthy behaviors), which has been used successfully in several areas, e.g. in social psychology, transport psychology. The volume of studies and the brigade of the elaborative work were prepared by dr. Malét-Szabó Erika and prof. dr. Ákos Münnich, furthermore we can thank the the colleagues of Professor Münnich at the University of Debrecen, who put together the content. In addition to these, dr. Judit Hegedüs, head of the Department of Behavioral Sciences at University of Publice Service Faculty of Law Enforcement, presents the practical experiences of the model.